2021
DOI: 10.1159/000511203
|View full text |Cite
|
Sign up to set email alerts
|

ALS-Like Disorder in Three HIV-Positive Patients: Case Series

Abstract: There appears to be a relationship between retroviruses such as HIV and the development of an ALS-like syndrome. Few cases have been reported; however, there exists evidence of a higher frequency of motor neuron disease in HIV-infected patients, as well as potential slowing and reversibility of disease course with combination antiretroviral therapy. We conducted a retrospective chart review of patients presenting to the George Washington University ALS Clinic from September 2006 to June 2018 to identify patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…The majority of cases in this study were of primary origin with only 5 cases imputed to syphilis. HIV-associated ALS has also been reported in other series [ 36 ].…”
Section: Discussionsupporting
confidence: 64%
“…The majority of cases in this study were of primary origin with only 5 cases imputed to syphilis. HIV-associated ALS has also been reported in other series [ 36 ].…”
Section: Discussionsupporting
confidence: 64%
“…While many studies have reported the beneficial clinical effect of ARV therapy on a patient's outcome, her weakness progressed after one year of ARV therapy. However, a case report study by Satin et al, demonstrated three patients with HIV-associated ALS with mixed UMN and LMN involvement and slow disease progression with proper clinical response to ARV therapy (6). Unlike clinical response in our patient, MacGowan et al, reported a 32-year-old woman with HIVassociated ALS who recovered from motor neuron deficit after initiation of ARV therapy (7).…”
Section: Discussionmentioning
confidence: 48%
“…Previous studies of HIV patients shed further light on the importance of the systemic immune system in ALS. These studies reported that HIV patients are more likely to exhibit an ALS-like syndrome, and this condition improves after anti-HIV treatment (Satin and Bayat 2021; Bowen et al 2016; MacGowan et al 2001; Quevedo-Ramirez et al 2020; Verma and Berger 2006). Relative to the studies of motor neurons and glial cells in ALS, much less work has been done on the systemic aspect of ALS.…”
Section: Resultsmentioning
confidence: 99%